9(t-6)+5t=7(2t+5)-12

Simple and best practice solution for 9(t-6)+5t=7(2t+5)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(t-6)+5t=7(2t+5)-12 equation:


Simplifying
9(t + -6) + 5t = 7(2t + 5) + -12

Reorder the terms:
9(-6 + t) + 5t = 7(2t + 5) + -12
(-6 * 9 + t * 9) + 5t = 7(2t + 5) + -12
(-54 + 9t) + 5t = 7(2t + 5) + -12

Combine like terms: 9t + 5t = 14t
-54 + 14t = 7(2t + 5) + -12

Reorder the terms:
-54 + 14t = 7(5 + 2t) + -12
-54 + 14t = (5 * 7 + 2t * 7) + -12
-54 + 14t = (35 + 14t) + -12

Reorder the terms:
-54 + 14t = 35 + -12 + 14t

Combine like terms: 35 + -12 = 23
-54 + 14t = 23 + 14t

Add '-14t' to each side of the equation.
-54 + 14t + -14t = 23 + 14t + -14t

Combine like terms: 14t + -14t = 0
-54 + 0 = 23 + 14t + -14t
-54 = 23 + 14t + -14t

Combine like terms: 14t + -14t = 0
-54 = 23 + 0
-54 = 23

Solving
-54 = 23

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -2(-6w+8)-6w=2(w-1)-8 | | 10n=92+21 | | j^7*j^1= | | 69=(r)23 | | 15=4(y+11) | | 3/8-1/12=x/3 | | 4+8+x=19 | | -8/5 | | 7x+15=7x-15 | | 625(.056)+25(.04c)+c=35 | | 2*x+x=60 | | w^2+13w-2=0 | | 625(.056)+25b+c=35 | | 12x+24(x-5)=56x | | 15=14(y+11) | | .98(x)=18 | | -5c=50 | | 55(8+3)=h | | 4225a+65b+c=310 | | 6=r-70/3 | | (3z+5)+(6z+4)=9z+9 | | 2025a+45b+c=115 | | x^2+3x-(x-4)=28 | | 3/5X15/2= | | y=-7.3x^2+8.25x+2.1 | | 3(4t+32)-8=46 | | 4x+3y+11x-2y= | | 3-3=6x+4x | | 13=10x+30 | | (3(y-2))/5=1-3y | | F=wr | | 6x+2x+x=144 |

Equations solver categories